Determination of the stages of deep pectoral myopathy induced in broilers fed with supplemental coenzyme q10 - Zlatko JOJKIC; Slobodan STOJANOVIC; Dragan ZIKIC; Sinisa BJEDOV; Verica MILOSEVIC; Marko MILER; Gordana USCEBRKA (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2018)
The aim of this study was to examine the structural characteristics and incidence of different stages of deep pectoral myopathy (DPM) that was induced in broilers fed a coenzyme Q10 (CoQ10) supplemented diet. A total of 288 1-day-old chicks (Cobb 500) were equally divided among 8 pens (pens 1 to 8). The diet was the same for all chicks until day 35 post-hatching. Subsequently, broilers in pens 5 to 8 were fed the 20 mg of CoQ10/kg finisher diet until the end of the experiment (day 42 post-hatching). To induce DPM, 5 male birds from each of the pens 1 to 8 were subjected to encouraged wing flapping (EWF) at the end of their 37th day. At the end of the trial, the incidence of DPM stages in broilers was determined and an analysis of the histological parameters of deep pectoral muscles was performed. Results showed that, in the groups subjected to EWF, broilers with the CoQ10 supplement had a lower average DPM stage and volume density of necrotic muscle cells, as well as a higher volume density of non-necrotic muscle cells. These results can be related to the antioxidant properties of CoQ10, which, in chickens subjected to EWF, reduced the effects of DPM on cell necrosis and muscle tissue damage.